2018
DOI: 10.1186/s12986-018-0251-5
|View full text |Cite|
|
Sign up to set email alerts
|

Current therapies in alleviating liver disorders and cancers with a special focus on the potential of vitamin D

Abstract: BackgroundLiver dysfunction is a topic of global concern with many advancing therapies being researched. Though vitamin D takes a center place, other therapies especially nutritional are also gaining ground. Vitamin D has gone beyond its role in skeletal disorders by showcasing its associations in other metabolic dysfunctions too.ResultEpidemiological evidences show a correlation between the status of vitamin D and different forms of cancer. Vitamin D receptors and alterations in gene expression appear decisiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 196 publications
(177 reference statements)
0
7
0
Order By: Relevance
“…Early diagnosis, optimizing vitamin D status, and early initiation of immunosuppressive therapy are recommended. The potential role of low vitamin D status to cause muscle weakness especially in cancer patients and possible positive immunomodulatory effects were considered [74,75] for the above recommendations. IVIg induction dose of 2 g/kg divided over 2-5 days and maintenance 1 g/kg, with a maximum of 60 g given every 2-3 weeks depending to the clinical response, can be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis, optimizing vitamin D status, and early initiation of immunosuppressive therapy are recommended. The potential role of low vitamin D status to cause muscle weakness especially in cancer patients and possible positive immunomodulatory effects were considered [74,75] for the above recommendations. IVIg induction dose of 2 g/kg divided over 2-5 days and maintenance 1 g/kg, with a maximum of 60 g given every 2-3 weeks depending to the clinical response, can be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ] one of the authors wrote to say that his name had been spelt incorrectly as Ahmed Makki instead of Ahmad Makki.…”
Section: Correctionmentioning
confidence: 99%
“…Additionally, it has multiple functions and target organs and influences the expression of several genes and plays important roles in the regulation of cell proliferation and differentiation, immune function, oxidative stress, protein glycation, inflammation, and apoptosis (7)(8)(9). Therefore, Vit D has been reported to be effective in preventing many diseases such as diabetes, hypertension, cardiovascular and hepatic diseases and cancer (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are some differences in clinical guidelines, the Institute of Medicine (Washington; USA) defines VDD as a 25(OH)D level of <20 ng/mL and severe VDD as <10 ng/mL (15). VDD alone may induce IR, oxidative stress, inflammation, and mitochondrial dysfunction (8,10,14). However, epidemiological and laboratory evidence have shown that VDD may be associated with some common diseases such as tumors, bone diseases, immune disorders, cardiovascular diseases, diabetes mellitus, and chronic liver disorders (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation